Pemikiran Islam dalam Menghadapi Cabaran Abad Ke 21M - Ab. Majid, Mohamad Kamil (Jurnal Usuluddin, 1995)
This article attempts to elaborate (the misconception regarding the meaning of thought in Islam and its difference from the teaching of Islam based on wahy a revealation. This article also discusses the contemporary and future challenges facing the thought, internal as well as external, civilizational, religious, cultural, technological and economic.